Markers of periodontal disease and cognitive decline in a diverse, older cohort. (31st December 2021) - Nikitin, Benjamin; Bahorik, Amber L; Mcevoy, Claire T; Yaffe, Kristine
Abstract: Background: Prior studies have reported associations between periodontitis, as a proxy for inflammation, and increased risk of cognitive decline and dementia, but findings for specific markers of periodontal disease (PDD) have been inconsistent with the few longitudinal studies in diverse cohorts. The goal of this study was to assess whether measures of PDD were associated with subsequent cognitive decline in a cohort of older Black and white adults. Method: We studied 967 Black and white adults, aged 70‐79 at baseline (51.8% female and 32.8% Black), enrolled in the Health, Aging and Body Composition study. Participants received a periodontal exam in year 2 which assessed indicators of PDD: gingival index (a rating of gingival inflammation), mean attachment loss, and mean pocket probing depth. Cognitive testing was repeated at baseline, years 3, 5, 8, 10, and 11, and included the Modified Mini‐Mental State (3MS) Examination and the Digit Symbol Substitution Test (DSST). We evaluated the association between PDD, categorized as tertiles, and cognitive decline over 11 years of follow‐up with linear mixed‐effects models. Result: In unadjusted models, higher gingival index was associated with greater decline on 3MS (high vs. low gingival index β = ‐0.27, 95% CI ‐0.48 to ‐0.05) but not DSST. This relationship remained significant after adjusting for race, sex, education, and socioeconomic status (β = ‐0.26, 95% CI ‐0.48 to ‐0.04). Models stratified by race suggest that this association was stronger among older Black adults (Black: β = ‐0.44, 95% CI ‐0.81 to ‐0.06; white: β = ‐0.13, 95% CI ‐0.40 to ‐0.12). Mean attachment loss and mean pocket probing depth were not consistently associated with cognitive decline. Conclusion: Gingival index was associated with worse decline in global cognition among Black and white older adults. Further work is necessary to understand other measures of poor oral health as markers of cognitive aging in diverse populations.